Factorize the following
Attachments:
![](https://hi-static.z-dn.net/files/da6/6feaa1d91f4eb645204f07e1bab1e391.jpg)
honeygarg21:
(x+1)(x-5)(x+1)
Answers
Answered by
1
Given Equation is x^3 - 3x^2 - 9x - 5
= > x^3 + x^2 - 4x^2 - 4x - 5x - 5
= > x^2(x + 1) - 4x(x + 1) - 5(x + 1)
= > (x^2 - 4x - 5)(x + 1)
= > (x^2 - 5x + x - 5)(x + 1)
= > (x(x - 5) + 1(x - 5))(x + 1)
= > (x + 1)(x - 5)(x + 1)
= > (x + 1)^2(x - 5).
Hope this helps!
Answered by
0
HOPE MY ANSWER IS RIGHT.
Attachments:
![](https://hi-static.z-dn.net/files/dfc/348fca3bd4131c432c8c232019594834.jpg)
Similar questions